2016
DOI: 10.3399/bjgp16x687961
|View full text |Cite
|
Sign up to set email alerts
|

Predicting clinical deterioration after initial assessment in out-of-hours primary care: a retrospective service evaluation

Abstract: Older, prior users of the service, presenting at less busy times, are at greater risk of requiring secondary care referral from the OOH service within 3 days of their initial contact. These higher-risk patient groups might benefit from active follow-up by the OOH service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…In the southwest of the UK, referrals to hospital from out-of-hours general practice were 9.2% between 2001 and 2004,15 and 9.5% in 2005/2006 16. In the Oxford area, 8.3% of patients seen in out-of-hours care were referred directly to secondary care 17. These are similar to the 8.5% overall referral rate in this cohort.…”
Section: Discussionsupporting
confidence: 74%
“…In the southwest of the UK, referrals to hospital from out-of-hours general practice were 9.2% between 2001 and 2004,15 and 9.5% in 2005/2006 16. In the Oxford area, 8.3% of patients seen in out-of-hours care were referred directly to secondary care 17. These are similar to the 8.5% overall referral rate in this cohort.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies identified characteristics associated with face-to-face contacts, onward referral to ED and subsequent contacts or escalation in care. Analysis of 4 years’ worth of OOHS contacts in one area of England showed that 1% (4832) of all OOHS contacts had a second OOHS contact within 3 days which resulted in referral to urgent secondary care services (eg, hospital admission, ED or immediate ambulance) 67. Increasing age, prior use of OOHS and presentation during periods of low contact rates (eg, overnight) were identified as patient factors associated with this ‘delayed escalation’.…”
Section: Resultsmentioning
confidence: 99%
“…Gastrointestinal conditions in particular have been highlighted previously as challenging to diagnose in prehospital urgent care settings. 13 14 Evolving OOH care services to include a greater range of point of care (POC) blood and imaging diagnostics and tailored risk scores could offer clinicians support in triaging and managing these difficult presentations.…”
Section: Discussionmentioning
confidence: 99%